PENENTUAN HARGA POKOK PRODUKSI PADA USAHA MOULDING UD. KEMBAR MAS SAMARINDA - Liso, La (EKONOMIA, 2013)
LA LISO , 2013 S - 1 Program , Faculty of Economics, University of Samarinda August 17, 1945 , Determination of Cost of Production In Moulding Enterprises UD . Mas twin Samarinda , Titin Ruliana Supervisor I , Advisor II Suyatin . Efforts related to housing became a very lucrative business , given not only the building materials are a top priority in housing construction but also the framework of the house itself must be considered . One of the businesses that provide these services are UD molding business . Mas twin Samarinda . These efforts serve to create the framework of the house such as sills , doors , windows , and various other orders related to logging and marketing efforts include the city of Samarinda . This study was conducted to clarify the calculation of the order cost door bengkirai 7 ( seven ) lower panel compared to calculations made by the company . calculation of the company with the adoption of the order cost . Production costs are those costs that occur within the manufacture of finished products . Elements of production costs is what will form the cost of production , in which the elements consist of raw material costs , labor costs and factory overhead costs . From the results of this study is that There are differences in the calculation of the cost of production for 7 door panel orders that the difference of Rp . 500.543 .-/unit . According to the company's calculation of the cost is Rp . 631,785.713 , -/unit . Meanwhile, according to calculations performed by the authors using the cost of the order on the basis of allocation of manufacturing overhead costs using the relative selling price is Rp . 631,285.17 .-/unit with this calculation will increase the cost of production . With this shows that , the existence of specialized judicial institutions in a State law is very important and vital for the existence of judicial institutions are given special authority to conduct law enforcement more specifically , the purpose is to create a sense of justice through the courts with special handling special . As suggestions submitted in research that , in order to calculate the cost of production is produced by the method of the order cost , because then it is known for sure the amount of the costs incurred for the actual production process occurs can be reduced cost and selling price can be lowered